2017
DOI: 10.1101/172635
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Integrator Subunit 4 is a ‘Symplekin-like’ Scaffold that Associates with INTS9/11 to Form the Integrator Cleavage Module

Abstract: Integrator (INT) is a transcriptional regulatory complex associated with RNA polymerase II that is required for the 3'-end processing of both UsnRNAs and enhancer RNAs. Integrator subunits 9 (INTS9) and INTS11 constitute the catalytic core of INT and are paralogues of the cleavage and polyadenylation specificity factors CPSF100 and CPSF73. While CPSF73/100 are known to associate with a third protein called Symplekin, there is no paralog of Symplekin within INT raising the question of how INTS9/11 associate wit… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 19 publications
(46 citation statements)
references
References 57 publications
(74 reference statements)
2
44
0
Order By: Relevance
“…The Integrator complex has been implicated in a myriad of diseases, interacts with RNAPII, and contains the IntS11 RNA endonuclease that generates the 3′ ends of spliceosomal snRNAs (Baillat et al 2005;Baillat and Wagner 2015). We confirmed that depleting subunits of the Integrator cleavage module (IntS4, IntS9, or IntS11) resulted in increased snRNA readthrough transcription (Ezzeddine et al 2011;Albrecht et al 2018) (Fig. 1E; Supplemental Fig.…”
Section: Mtna Promoter During Copper Stresssupporting
confidence: 63%
See 1 more Smart Citation
“…The Integrator complex has been implicated in a myriad of diseases, interacts with RNAPII, and contains the IntS11 RNA endonuclease that generates the 3′ ends of spliceosomal snRNAs (Baillat et al 2005;Baillat and Wagner 2015). We confirmed that depleting subunits of the Integrator cleavage module (IntS4, IntS9, or IntS11) resulted in increased snRNA readthrough transcription (Ezzeddine et al 2011;Albrecht et al 2018) (Fig. 1E; Supplemental Fig.…”
Section: Mtna Promoter During Copper Stresssupporting
confidence: 63%
“…Therefore, we did not induce metal stress in subsequent experiments. Upon depleting each Integrator subunit individually, we noted that expression of these mRNAs was often most affected by depletion of IntS4, which forms the scaffold of the Integrator cleavage module (Albrecht et al 2018) (Fig. 5C; Supplemental Fig.…”
Section: Many Drosophila Protein-coding Genes Are Controlled By the Imentioning
confidence: 99%
“…It is unknown whether these association phenomena are biologically relevant, and few studies have reported the impact of depletion of one nuclear body upon the function of other structures (Tapia et al, ). However, we have previously shown that Cajal body disassembly perturbs spatial gene positioning and expression of histone mRNAs, presumably through its association with the HLB in transformed human cells (Albrecht et al, ; Wang et al, ). The biochemical rationale for these physical spatial interactions is unknown but can be speculated upon.…”
Section: Mlo Cooperativity and Rna/protein Sharingmentioning
confidence: 99%
“…Our understanding of how and why these structures physically interact will be illuminated by SRM co‐localization of proteins enriched in separate nuclear bodies, and a better grasp of their ability to supply or sequester components (Sawyer, Bartek, & Dundr, ). The frequent physical association between the Cajal body and the HLB may represent a good model for further analysis of internuclear body surface interaction dynamics by SRM (Albrecht et al, ; Sawyer, Hager, & Dundr, ; Wang et al, ). Indeed, how the physical surface interaction dynamics between two distinct nuclear bodies varies under different physiological conditions is an outstanding question.…”
Section: Mlo Cooperativity and Rna/protein Sharingmentioning
confidence: 99%
“…Critical among its protein components is Integrator subunit 11 (INTS11) , which is a member of the metallo-β-lactamase/β-CASP family of RNA endonucleases 31 and is a paralog of the cleavage and polyadenylation specificity factor of 73 kDa (CPSF73), which cleaves pre-mRNA 32 . INTS11 has been found to associate with INTS4 and INTS9 to form what is called the Integrator Cleavage Module (CM), which is thought to be the key enzymatic factor within the complex 33 . The Integrator CM, through the activity of INTS11, has been shown to be essential to cleave the 3' ends of a variety of noncoding RNA and nascent mRNA of protein-coding genes with paused RNAPII.…”
Section: Introductionmentioning
confidence: 99%